Assessment Study of Adversity Quotient and Servant Leadership to Improve Organizational Citizenship Behavior: Strengthening Managerial Competencies of Education Leader - Nurbianta Nurbianta; Joe Bren Consuelo; Ahmadong Ahmadong; Aria Nur Farida Muslicha (Universitas Ahmad Dahlan, 2022)
The main objective of this study was to explain the improvement of organizational citizenship behavior through adversity quotient and servant leadership as an effort to improve the managerial competence of educational leaders. The research subject was principals of senior high school in Berau. Meanwhile, specifically, the objectives were; (1) to seek whether there is the relationship between adversity quotient and organizational citizenship behavior, (2) to seek whether there is the relationship between servant leadership and organizational citizenship behavior, (3) to seek whether there is the relationship between adversity quotient and servant leadership to organizational citizenship behavior simultaneously. This study concerned a quantitative analysis by testing hypotheses using the statistic tool of the SITOREM model. The finding shows; that (1) there is a relationship between adversity quotient and organizational citizenship behavior, (2) there is the relationship between servant leadership and organizational citizenship behavior, and (3) there is the relationship between adversity quotient and servant leadership to organizational citizenship behavior simultaneously. In other words, it shows that the primary purpose of this research is achieved because the adversity quotient and servant leadership can result in the creation of good organizational citizenship behavior. Indeed this can also indicate that the principal has the managerial competence of educational leaders in an organization/school favorable.